Efektivitas Pengelolaan Anggaran Penanganan Pelanggaran Pemilu Presiden Pada Bawaslu Dki Jakarta Tahun 2024 - Marcellinus Ferrer Wandra Sihaloho; Riki Satia Muharam (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
Budget management for handling violations of the 2024 Presidential Election at the Election Supervisory Board of DKI Jakarta Province played a crucial role in ensuring effective election oversight and law enforcement. This study was conducted to analyze the effectiveness of budget management for handling presidential election violations in DKI Jakarta. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and document analysis, including budget documents, realization reports, and activity reports related to violation handling. The findings revealed that budget management had been fairly effective in supporting violation handling, particularly in ensuring timely case resolution and coordination across supervisory levels. However, limitations were identified in budget flexibility, accuracy of needs estimation, and administrative complexity during peak election periods. The study implies the importance of more adaptive budget planning, streamlined administrative procedures, and strengthened human resource capacity. The originality of this research lies in its focus on budget management effectiveness within the context of presidential election violation handling in a politically dynamic metropolitan area.